Optimizing the flavanone core toward new selective nitrogen-containing modulators of ABC transporters. (23rd March 2018) - Ferreira, Ricardo J; Baptista, Rafael; Moreno, Alexis; Madeira, Patricia G; Khonkarn, Ruttiros; Baubichon-Cortay, Hélène; dos Santos, Daniel JVA; Falson, Pierre; Ferreira, Maria-José U
Aim: Naringenin (1 ), isolated in large amount from the aerial parts of Euphorbia pedroi, was chemically derivatized to yield 18 imine derivatives (2–19 ) and three alkylated derivatives through a Mannich-type reaction (20–22 ) that were tested as multidrug resistance (MDR) reversers in cancer cells.Results/methodology: While hydrazone (2–4 ) and azine (5–13 ) derivatives showed an improvement in their MDR reversal activities against the breast cancer resistance protein, carbohydrazides14–19 revealed an enhancement in MDR reversal activity toward the multidrug resistance protein 1.Conclusion: The observed activities, together with pharmacophoric analysis and molecular docking studies, identified the spatial orientation of the substituents as a key structural feature toward a possible mechanism by which naringenin derivatives may reverse MDR in cancer.